Pemberdayaan Desa Melalui Pelatihan Edugame Wordwall: Meningkatkan Literasi Digital, Keterampilan Sosial, dan Ekspresi Emosi Anak Usia Dini [Village Empowerment Through Edugame Wordwall Training: Enhancing Digital Literacy, Social Skills, and Emotional Expression in Early Childhood] - Hardiningrum, Andini; Shari, Destita; Basuki, Edi Pujo; Ningrum, Anisa Aulia; Saputro, Trisna Fellycia Nur (UKInstitute, 2025)
Abstract. This activity is motivated by the low digital literacy of educators in the village, which has resulted in suboptimal development of social skills and emotional expression in early childhood. The implementation of Wordwall was chosen because it supports creative and enjoyable learning in the digital era. This community service aims to improve the skills of early childhood education (PAUD) teachers in Jabaran Village in utilizing the Wordwall platform as an interactive digital-based learning medium. The method uses a participatory approach with three stages: needs identification through surveys and interviews, conducting theory and practical Wordwall training over three days, and evaluating the impact on teaching practices. The training participants consisted of PAUD teachers in Jabaran Village who actively engaged in all stages. Data were collected through observation, questionnaires, and interviews, then analyzed descriptively and qualitatively. The results showed a significant increase in teachers' understanding and skills in using Wordwall, from 30% previously to 95%. Children showed increased active engagement in class, with participation and positive response indicators rising by more than 40%. Teachers became more innovative and confident in developing game-based learning media. This training proved effective in reducing the digital gap and supporting children's social-emotional development. The activity demonstrated that digital training based on edugames can be an effective strategy for empowering village communities, especially in early childhood education. It is hoped that this program will serve as a model for developing similar training in other villages as an effort to support equitable access to education in the digital era. Abstrak. Kegiatan ini dilatarbelakangi oleh rendahnya literasi digital pendidik di desa yang berdampak pada kurang optimalnya pengembangan keterampilan sosial dan ekspresi emosi anak usia dini. Penerapan Wordwall dipilih karena mampu mendukung pembelajaran yang kreatif dan menyenangkan di era digital. Pengabdian kepada masyarakat ini bertujuan meningkatkan keterampilan guru PAUD di Desa Jabaran dalam memanfaatkan platform Wordwall sebagai media pembelajaran interaktif berbasis digital.Metode pelaksanaan menggunakan pendekatan partisipatif dengan tiga tahapan: identifikasi kebutuhan melalui survei dan wawancara, pelaksanaan pelatihan teori dan praktik Wordwall selama tiga hari, serta evaluasi dampak terhadap praktik pengajaran. Peserta pelatihan terdiri dari guru-guru PAUD di Desa Jabaran yang secara aktif terlibat dalam semua tahapan. Data dikumpulkan melalui observasi, angket, dan wawancara, lalu dianalisis secara deskriptif kualitatif. Hasil menunjukkan peningkatan signifikan pada pemahaman dan keterampilan guru dalam menggunakan Wordwall, dari sebelumnya 30% menjadi 95%. Anak-anak menunjukkan peningkatan keterlibatan aktif di kelas, dengan indikator partisipasi dan respons positif meningkat lebih dari 40%. Guru menjadi lebih inovatif dan percaya diri dalam mengembangkan media pembelajaran berbasis permainan. Pelatihan ini terbukti efektif dalam mengurangi kesenjangan digital serta mendukung perkembangan sosial-emosional anak. Kegiatan ini membuktikan bahwa pelatihan digital berbasis edugame dapat menjadi strategi efektif dalam pemberdayaan masyarakat desa, khususnya di bidang pendidikan anak usia dini. Diharapkan program ini menjadi model bagi pengembangan pelatihan serupa di desa lain sebagai upaya mendukung pemerataan akses pendidikan di era digital.